Determination of α-Tocopherol in Plasma by High Performance Liquid Chromatography with Fluorescence Detection and Stability of α-Tocopherol under Different Conditions - Rümelin, Andreas; Humbert, Till; Fauth, Ulrich (Arzneimittelforschung, 2004)
In order to study the clinical effects of the antioxidant α-tocopherol (tocofersolan, CAS 30999-06-5) a simple, robust, sensitive and reliable high performance liquid chromatography (HPLC) method using fluorescence detection for the daily measurement of α-tocopherol concentration in plasma is described. Several methods of HPLC analysis using fluorescence techniques are published, however, investigations of the stability of α-tocopherol during sample preparation under different conditions are relevant in the routine measurements and have to date not been reported.Therefore a modified method, both sensitive and robust, qualified for the day-by-day measurement of α-tocopherol in plasma was established and the stability of α-tocopherol during sample preparation was analysed under different conditions. This method enables the complete separation of α-tocopherol from other compounds within 14 min. In addition, investigations on the stability of α-tocopherol during sample preparation showed the necessity of rapid sample preparation without delay. Prepared samples can be stored in liquid nitrogen for at least 56 days.
Keywords: CAS 30999-06-5; Tocofersolan; α-Tocopherol, determination in plasma, stability; Vitamin E